Penalaran Induktif Peserta Didik SMP dalam Menyelesaikan Soal Matematika Ditinjau dari Perbedaan Jenis Kelamin - Aulia Putri Marwah; Pradnyo Wijayanti (MATHEdunesa, 2026)
Inductive reasoning is one of the skills required to solve mathematics problems. As a cognitive process, inductive reasoning is influenced by many factors, including gender differences. This study aims to describe students' inductive reasoning in solving mathematics problems based on gender differences. This research is a descriptive study with a qualitative approach. The subjects were two eighth-grade students from SMPN 6 Tulungagung during the 2024/2025 academic year: one male student and one female student, both with equivalent mathematical abilities. Data collection methods included tests and interviews. Inductive reasoning was analyzed based on the following indicators used by the researcher: (1) observation on particular cases, (2) organization of particular cases, (3) search and prediction patterns, (4) conjecture formulation, (5) conjecture validation, (6) conjecture generalization, and (7) general conjecture justification. The research results indicate that both students observed specific cases, managed specific cases, searched for and conjectured patterns, conjectured formulas, validated conjectures, generalized conjectures, and justified general conjectures. The differences lay in how they acquired initial knowledge and their conjecture validation strategies. The male student acquired initial knowledge based on previously known information and validated conjectures more than once, while the female student acquired initial knowledge based on direct measurement results with the help of a protractor and validated conjectures only once.